Discovery of new phenyl sulfonyl-pyrimidine carboxylate derivatives as the potential multi-target drugs with effective anti-Alzheimer's action: Design, synthesis, crystal structure and in-vitro biological evaluation - Manzoor S.; Prajapati S.K.; Majumdar S.; Raza K.; Gabr M.T.; Kumar S.; Pal K.; Rashid H.; Kumar S.; Krishnamurthy S.; Hoda N. (My University, 2025)
Alzheimer's disease (AD) is multifactorial, progressive neurodegeneration with impaired behavioural and cognitive functions. The multitarget-directed ligand (MTDL) strategies are promising paradigm in drug development, potentially leading to new possible therapy options for complex AD. Herein, a series of novel MTDLs phenylsulfonyl-pyrimidine carboxylate (BS-1 to BS-24) derivatives were designed and synthesized for AD treatment. All the synthesized compounds were validated by 1HNMR, 13CNMR, HRMS, and BS-19 were structurally validated by X-Ray single diffraction analysis. To evaluate the plausible binding affinity of designed compounds, molecular docking study was performed, and the result revealed their significant interaction with active sites of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). The synthesized compounds displayed moderate to excellent in vitro enzyme inhibitory activity against AChE and BuChE at nanomolar (nM) concentration. Among 24 compounds (BS-1 to BS-24), the optimal compounds (BS-10 and BS-22) displayed potential inhibition against AChE; IC50 = 47.33 ± 0.02 nM and 51.36 ± 0.04 nM and moderate inhibition against BuChE; IC50 = 159.43 ± 0.72 nM and 153.3 ± 0.74 nM respectively. In the enzyme kinetics study, the compound BS-10 displayed non-competitive inhibition of AChE with Ki = 8 nM. Respective compounds BS-10 and BS-22 inhibited AChE-induced Aβ1-42 aggregation in thioflavin T-assay at 10 μM and 20 μM, but BS-10 at 10 μM and 20 μM concentrations are found more potent than BS-22. In addition, the aggregation properties were determined by the dynamic light scattering (DLS) and was found that BS-10 and BS-22 could significantly inhibit self-induced as well as AChE-induced Aβ1-42 aggregation. The effect of compounds (BS-10 and BS-22) on the viability of MC65 neuroblastoma cells and their capability to cross the blood-brain barrier (BBB) in PAMPA-BBB were further studied. Further, in silico approach was applied to analyze physicochemical and pharmacokinetics properties of the designed compounds via the SwissADME and PreADMET server. Hence, the novel phenylsulfonyl-pyrimidine carboxylate derivatives can act as promising leads in the development of AChE inhibitors and Aβ disaggregator for the treatment of AD. © 2021 Elsevier Masson SAS